Improving the Microenvironmental of Spring Soybean Culture and Increasing the Yield by Optimization of Water and Nitrogen - Lei Zhang; Hongbo Wang; Yang Gao; Weixiong Huang; Zhenxi Cao; Maosong Tang; Fengnian Zhao; Yuanhang Guo; Xingpeng Wang (Agronomy)
Optimizing water and nitrogen management is an effective measure to reduce nitrogen fertilizer loss and environmental pollution risks. This study aims to quantify the impacts of different water and nitrogen management strategies on the soil microenvironment and yield of spring soybeans in southern Xinjiang. In this study, two irrigation quotas were established: W1—36 mm (low water) and W2—45 mm (high water). Three nitrogen application gradients were established: low nitrogen (150 kg·hm−2, N1), medium nitrogen (225 kg·hm−2, N2), and high nitrogen (300 k kg·hm−2, N3). The analysis focused on soil physicochemical properties, enzyme activities, microbial community diversity, soybean yield, and soybean quality changes. The results indicate that the activities of nitrate reductase and urease, as well as total nitrogen content, increased with higher irrigation and nitrogen application rates. The W2N3 treatment significantly increased 0.15 to 4.39, 0.18 to 1.04, and 0.31 to 1.73 times. (p < 0.05). Alkaline protease and sucrase activities increased with higher irrigation amounts, while their response to nitrogen application exhibited an initial increase followed by a decrease. The W2N2 treatment significantly increased by 0.10 to 0.34 and 0.07 to 1.46 times (p < 0.05). Irrigation significantly affected the soil bacterial community structure, while the coupling effects of water and nitrogen notably influenced soil bacterial abundance (p < 0.05). Increases in irrigation and nitrogen application enhanced bacterial diversity and species abundance. Partial least squares path analysis indicated that water–nitrogen coupling directly influenced the soil microenvironment and indirectly produced positive effects on soybean yield and quality. An irrigation quota of 4500 m3 hm−2 and a nitrogen application rate of 300 kg·hm−2 can ensure soybean yield while enhancing soil microbial abundance. The findings provide insights into the response mechanisms of soil microbial communities in spring soybeans to water–nitrogen management, clarify the relationship between soil microenvironments and the yield and quality of spring soybeans, and identify optimal irrigation and fertilization strategies for high quality and yield. This research offers a theoretical basis and technical support for soybean cultivation in southern Xinjiang.